2004
DOI: 10.3748/wjg.v10.i12.1822
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of human primary gastric carcinoma cells induced by genistein

Abstract: AIM:To investigate the apoptosis in primary gastric cancer cells induced by genistein, and the relationship between this apoptosis and expression of bcl-2 and bax. METHODS:MTT assay was used to determine the cell growth inhibitory rate in vitro. Transmission electron microscope and TUNEL staining were used to quantitatively and qualitatively detect the apoptosis of primary gastric cancer cells before and after genistein treatment. Immunohistochemical staining and RT-PCR were used to detect the expression of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In preclinical models, genistein was able to induce apoptosis in primary gastric cancer cells (20 mM for 24-72 h) by downregulating the expression of the antiapoptotic protein B cell lymphoma 2 (Bcl-2) and upregulating the expression of proapoptotic Bcl-2-associated X protein (Bax) (117). A similar modification of the Bcl-2:Bax ratio was considered responsible for the ability of genistein (0.5, 1, and 1.5 mg/kg) to induce apoptosis in SG7901 cells transplanted into subcutaneous tissue of nude mice (118).…”
Section: Genistein and Cancermentioning
confidence: 99%
“…In preclinical models, genistein was able to induce apoptosis in primary gastric cancer cells (20 mM for 24-72 h) by downregulating the expression of the antiapoptotic protein B cell lymphoma 2 (Bcl-2) and upregulating the expression of proapoptotic Bcl-2-associated X protein (Bax) (117). A similar modification of the Bcl-2:Bax ratio was considered responsible for the ability of genistein (0.5, 1, and 1.5 mg/kg) to induce apoptosis in SG7901 cells transplanted into subcutaneous tissue of nude mice (118).…”
Section: Genistein and Cancermentioning
confidence: 99%
“…Isoflavones, such as genistein and daidzein, directly affect gastric cancer cells (11,22,23). Genistein could participate in apoptosis by downregulation of apoptosis-regulated gene Bcl2 and upregulation of apoptosis-regulated gene Bax (38,39). Additionally, genistein could inhibit gastric cancer cell growth and proliferation by cell cycle arrest at G 2 and early M phase and angiogenesis and induce cell apoptosis (11,22); daidzein could inhibit gastric cancer cell growth by cell cycle arrest at G 1 phase (22).…”
Section: Discussionmentioning
confidence: 99%
“…The results from our laboratory and other investigators showed that isoflavone inhibited the growth of various cancer cells, including leukemia, lymphoma, neuroblastoma, breast, prostate, lung, gastric, ovarian, and head and neck cancer cells (1,21,29,32,45,70,78,81,127). The inhibition of cancer growth by isoflavone could be mediated by the induction of apoptosis and the modulation of expression of the genes related to the cell growth and apoptotic processes (1,70,78,81,128).…”
Section: The Inhibitory Effects Of Isoflavone On Cancermentioning
confidence: 71%
“…The isoflavone genistein also inhibited constitutive and inducible NF-jB activation and decreased IL-8 production in human cystic fibrosis bronchial gland cells (115). It is also reported that isoflavone inhibited NF-jB activation in various solid cancers, including neuroblastoma, breast, prostate, lung, gastric, ovarian, and head and neck cancer cells (1,32,45,78,81,127), suggesting that downregulation of NF-jB signaling is an important mechanism by which isoflavone functions as an antioxidant, and thereby inhibits cancer development and progression (Fig. 4).…”
Section: Inhibition Of Oxidative Stress and Nf-kb Activation By Isoflmentioning
confidence: 89%